PA3297 Counteracts Antimicrobial Effects of Azithromycin in Pseudomonas aeruginosa - Tan, Hao; Zhang, Lu; Weng, Yuding; Chen, Ronghao; Zhu, Feng; Jin, Yongxin; Cheng, Zhihui; Jin, Shouguang; Wu, Weihui (Frontiers in Microbiology, 2016)
Pseudomonas aeruginosa causes acute and chronic infections in human. Its increasing resistance to antibiotics requires alternative treatments that are more effective than available strategies. Among the alternatives is the unconventional usage of conventional antibiotics, of which the macrolide antibiotic azithromycin (AZM) provides a paradigmatic example. AZM therapy is associated with a small but consistent improvement in respiratory function of cystic fibrosis (CF) patients suffering from chronic P. aeruginosa infection. Besides immunomodulating activities, AZM represses bacterial genes involved in virulence, quorum sensing, bioﬁlm formation, and motility, all of which are due to stalling of ribosome and depletion of cellular tRNA pool. However, how P. aeruginosa responds to and counteracts the effects of AZM remain elusive. Here we found that deficiency of PA3297, a gene encoding a DEAH-box helicase, intensified AZM-mediated bacterial killing, suppression of pyocyanin production and swarming motility, and hypersusceptibility to hydrogen peroxide. We demonstrated that expression of PA3297 is induced by the interaction between AZM and ribosome. Importantly, mutation of PA3297 resulted in elevated levels of unprocessed 23S-5S rRNA in the presence of AZM, which might lead to increased susceptibility to AZM-mediated effects. Our results revealed one of the bacterial responses in counteracting the detrimental effects of AZM.